Unit-root tests based on forward and reverse Dickey-Fuller regressions (2018)
In this article, we present the command adfmaxur, which computes the Leybourne (1995, Oxford Bulletin of Economics and Statistics 57: 559-571) unit-root statistic for different numbers of observations and the number of lags of the dependent variable in the test regressions. The latter can be either specified by the user or endogenously determined. We illustrate the use of adfmaxur with an empirical example. © 2018 StataCorp LLC.